Davao Light and Power Company's corporate social responsibilities (CSR) and the effectiveness of the skills development program a case study - Nombrado, Lady Dianne S.
Davao Light and Power Company (DLPC) os the sole provider of electricity in the city and has no competitor tod date. It is owned by the Aboitiz Group of Companies and has franchises up to Carmen, Panabo, Sto. Tomas. DLPC being one pf the largest companies in the city is presumed to have numerous CSR programs as part of their PR tool, however, the public is not aware of it. Thus, this study aimed to know the different CSR programs of the company, skills and development program, to be effective or not. Corporate Social Responsibility (CSR), also called corporate responsibility, corporate citizenship, responsible business and corporate social opportunity is a concept whereby organizations consider interests of society by taking responsibility for the impact of their activities on customers, suppliers, employees, shareholders, communities, and other stakeholders, as well as the environment. Knowing the effectiveness of a certain CSR program provides the basis for learning and improvement; informs the future planning and sheds light on both organizational and individual performance. Also finding out the CSR programs and its effectiveness of the issues an organization is focusing on. With the help of DLPC's Corporate Relations Head, Mr. Vic Sumalinog and the seven beneficiaries from OLVTC, the researcher was able to study and evaluate DLPC's CSR programs and the impact of the Skills Development Program towards the beneficiaries. The researcher found the Skills Development Program of DLPC ineffective despite the positive feedback of the beneficiaries. There is no evidence yet to show that DLPC's Skills Development has directly uplifted the standards of living of the beneficiaries. However, the program has taught the beneficiaries skills they could use when they would leave the center. Also, the company's Skills Development Program changed the beneficiaries' lifestyle ad the way they perceived DLPC's role. They now have a positive perception of the company after they benefited from the Skills Development Program. To make the Skills Development Program effective, DLPC should maintain relation and communication with their beneficiaries even after they leave the center to be able to know if the goal of their Skills Development Program has been achieved.